RISK ASSESSMENT FOR SMALL-SCALE ARCHITECTURE FIRM CASE STUDY: ARH ARCHITECT (The Indonesian Journal of Business Administration, 2021)
ARH Architect, an architectural firm based in Bandung established at the end of 2017, is a small-scale architecture firm. Services offered by ARH Architect are design and build, both scope in architectural design and interior design. A concern for small-scale architectural firms is unmeasurable risk in a business, especially in crises. Changes in market conditions, technological interventions, and the rapid development of trends have caused small-scale firms with supply chain and value chain difficulties to have a potential risk of high rate failure. The purpose of risk management needs to be done to minimize the risks that occur and help the firm achieve business goals. The research methodology in this study uses ISO 31000:2018 conceptual framework. The issue that happens in the firm’s business as a reference in implementing risk assessment. Risk assessment is used on the risks that happen in each category of the business model. The method of risk assessment in this research uses the qualitative risk analysis method. It aims to prioritize risks by classifying based on the possible impacts and risks in the business model aspect. Qualitative risk analysis can reduce uncertainty from risks with the highest priority likelihood and consequence identified in the business model. It is a method that has benefits in terms of cost and accuracy in setting priorities and planning the risk response in the business. Implementation plan of risk response based on preventive action and contingency plan in improving the existing business model. An implementation plan is a preventive action that focuses on minimizing the risk with the highest likelihood and impact levels. It refers to the risk prioritization identified in the previous phase. It affects the resources requirements and as an attempt by the firm to improvise on the business model aspect.Keywords: Risk Management, Business Model Risk, Architecture Firm